Examining the Bidirectional Relationship Between Entrepreneurship and Economic Growth: Is Entrepreneurship Endogenous? - Mojica-Howell, Maribel N.; Whittaker, Wesley L.; Gebremedhin, Tesfa G.; Schaeffer, Peter V. (IntechOpen, 2012)
None